Tie-up with German varsities boots UMP Grad's employability - UMP, LIB (The New Straits Times Press (M) Bhd., 2017)
KUANTAN: Universiti Malaysia Pahang (UMP) has succeeded in producing 95 per cent of employable graduates this year.